Sialylation regulates neutrophil transepithelial migration, CD11b/CD18 activation, and intestinal mucosal inflammatory function - Veronica Azcutia; Matthias Kelm; Dylan Fink; Richard D. Cummings; Asma Nusrat; Charles A. Parkos; Jennifer C. Brazil (JCI Insight, 2023)
Polymorphonuclear neutrophils (PMNs) play a critical role in clearing invading microbes and promoting tissue repair following infection/injury. However, dysregulated PMN trafficking and associated tissue damage is pathognomonic of numerous inflammatory mucosal diseases. The final step in PMN influx into mucosal lined organs (including the lungs, kidneys, skin, and gut) involves transepithelial migration (TEpM). The β2-integrin CD11b/CD18 plays an important role in mediating PMN intestinal trafficking, with recent studies highlighting that terminal fucose and GlcNAc glycans on CD11b/CD18 can be targeted to reduce TEpM. However, the role of the most abundant terminal glycan, sialic acid (Sia), in regulating PMN epithelial influx and mucosal inflammatory function is not well understood. Here we demonstrate that inhibiting sialidase-mediated removal of α2-3–linked Sia from CD11b/CD18 inhibits PMN migration across intestinal epithelium in vitro and in vivo. Sialylation was also found to regulate critical PMN inflammatory effector functions, including degranulation and superoxide release. Finally, we demonstrate that sialidase inhibition reduces bacterial peptide–mediated CD11b/CD18 activation in PMN and blocks downstream intracellular signaling mediated by spleen tyrosine kinase (Syk) and p38 MAPK. These findings suggest that sialylated glycans on CD11b/CD18 represent potentially novel targets for ameliorating PMN-mediated tissue destruction in inflammatory mucosal diseases.